Typology of Compulsory Will Arrangements in Some Muslim Countries - Dwi Sri Handayani (Hayula: Jurnal Indonesia Studi Islam Multi-disiplin, 2023)
This paper intends to look at the arrangements related to the provisions in the distribution of inheritance in several Muslim countries and group mandatory wills into clusters. This research uses a literature study (Library Research) that explores data based on pre-existing data with a comparative juridical approach that will be a comparison of laws from one country to another. The findings in this study that there are similarities and differences in the provisions of mandatory wills in various Muslim countries. The similarity can be seen from the clusters formed, namely there are 4 clusters related to the division of the State based on mandatory will regulations. The first cluster is Indonesia and Kuwait, the second cluster is Malaysia, Egypt and Tunisia. While the third cluster is Syria, Jordan, Morocco, and Syria. Then finally the fourth cluster is Pakistan, Turkey, Iraq and Iran. The four clusters have similarities that can be seen through: 1) the Provisions for Mandatory Wills and 2) the amount of inheritance obtained. While the difference lies in several grouping criteria, namely: 1) based on Islamic Law applied by Muslim countries, 2) the category of Mandatory Wills, 3) the Presntase of Mandatory Will Distribution, and 4) the requirements for the validity of determining heirs and the division of inheritance.